G. H. ZASS ON BATALPASHINSK PLOT LINE KUBAN (1833-1835) - Vladimir V. Parkhomenko (Вестник Северо-Кавказского федерального университета)
In this article examines the activities of G.H. Zass on the most dangerous section of the Kuban line. Studied the specifics of combat and defense organization. Considered the formation of G.H. Zass as an officer of the "Caucasian" type.